I write therefore I am : rewriting the subject in "The yellow wallpaper" and "The singing detective" : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University - Beatty, Bronwyn (Massey University. School of Social and Cultural Studies, 2001)
Focusing on "The Yellow Wallpaper" (1892) by Charlotte Perkins Gilman and "The Singing Detective" (1986) by Dennis Potter in dialogue with theories from Freud, Szasz, Foucault and Butler, my thesis considers the role of medicine in encouraging a patient toward a normative subjectivity. The protagonists of each text have become ill as a result of their inability to accept the social contradictions and lies upon which gendered subjectivity is reliant; the unnamed narrator of "The Yellow Wallpaper" comprehends femininity as servitude to male demands, while Marlow of The Singing Detective desires the power patriarchy offers him as a male, but his loss of belief and faith prevent his ascension to masculine status.Both the narrator of "The Yellow Wallpaper" and Marlow resist the imposition of normative gender by practitioners of mainstream medicine. Therefore, a more complex and subtle method of treatment, the psychoanalysis developed by Freud, is employed in The Singing Detective, thereby encouraging the patient to identify illness and discontent as personal, not societal, responsibility.I commence the thesis with an overview of the unequal power relations presupposed and encouraged by medical discourse. Through a process of 'hystericisation' the patient is infantilised and made dependent upon medical care. Linguistic control is central to manipulating patient behaviour within the hospital, and correspondingly the narrator of "The Yellow Wallpaper" and Marlow both seek a new subjectivity through their writing. Difficulties in appropriating language leads to internal incoherency for the protagonists, met by a split subjectivity - a defence mechanism which allows the protagonists to deviate from, at the same time as preserving, their 'good self'.The refusal of "The Yellow Wallpaper's" narrator to relinquish her defiant self and assume femininity is contained by patriarchy - embodied by her husband, John - as insanity. The strict limitation upon a nineteenth-century woman's expression prevents her from positively escaping her physician/husband's script leading to her mental demise. By contrast, Marlow successfully resocialises himself by modifying the hypermasculine persona he idealises, and is finally situated to confront and reform the social contradictions that precipitated his ill-health. However, subdued by having been led to identify discontent as a personal problem, Marlow is unlikely to challenge the power relations which have made his subjectivity possible. His capitulation to normalisation demonstrates a fundamental point linking the otherwise divergent theories of Freud and Foucault, that the creation of agency first requires the subject's subordination.
Keywords: "Yellow Wallpaper"; "Singing Detective"; Gender; Subjectivity; Power relations; Psychoanalytic interpretation; Literature, English; 420200 Literature Studies